The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/bf02982111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Subcutaneous Administration of a Low Dose of G-CSF on Stem Cell Mobilization in Healthy Donors: A Feasibility Study

Abstract: We investigated the effects of low-dose granulocyte colony-stimulating factor (G-CSF) on the mobilization of stem cells in 6 healthy subjects. When G-CSF was administered by continuous subcutaneous infusion at a rate of 72 microg/day for 5 days, the numbers of white blood cells and granulocytes rapidly increased to maximal levels. CD34+ cells were mobilized to the peripheral blood in 3 days, and the maximal level was reached 4 or 5 days after the start of treatment. We attempted to determine whether the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…It has been reported that G-CSF induces the mobilization of BMSCs from BM into the peripheral blood circulation (17). There were more capillaries in the border area of all the cytokine treatment groups with G-CSF than in control group after MI, and a part of the cells constituting the capillary wall were derived from BM cells.…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported that G-CSF induces the mobilization of BMSCs from BM into the peripheral blood circulation (17). There were more capillaries in the border area of all the cytokine treatment groups with G-CSF than in control group after MI, and a part of the cells constituting the capillary wall were derived from BM cells.…”
Section: Discussionmentioning
confidence: 80%
“…Cytokines and growth factors other than GM-CSF populate the tumor microenvironment and diffuse systemically in tumor-bearing hosts. CSF such as G-CSF, a glycoprotein that stimulates the release of white blood cells, particularly granulocytes and hematopoietic stem cells, into peripheral blood (54,55), is produced by squamous cells carcinomas of esophagus and tongue (56) and head and neck carcinomas (57,58). M-CSF, also known as CSF-1, has been detected in several human neoplasias such as acute myeloblastic leukemia (59,60), renal cell carcinoma (61), bladder carcinoma (62), and breast cancer, in which it seems to favor tumor progression and correlate with poor prognosis (63).…”
Section: Mdsc Recruiting and Activating Factorsmentioning
confidence: 99%
“…Bone marrow stem cells (BMSCs) differentiate into cardiomyocytes and endothelial cells and may participate in the regeneration of cardiac lesions (1)(2)(3)(4). Granulocyte colonystimulating factor (G-CSF) increased the number of peripheral granulocytes (5) and induced the mobilization of BMSCs to the periphery (6). This property and regenerative capacity of BMSCs justify the efforts to prove the efficacy of this therapy.…”
mentioning
confidence: 99%